Evaluating Alternatives to Cold Stabilization in Wineries: The Use of Carboxymethyl Cellulose, Potassium Polyaspartate, Electrodialysis and Ion Exchange Resins - Maria Pilar Martínez-Pérez; Ana Belén Bautista-Ortín; Valerie Durant; Encarna Gómez-Plaza (Foods, 2020)
The tartaric stabilization of wines before bottling to avoid the precipitation of tartaric acid salts is an important and common step during wine production. The presence of precipitated salt crystals in bottled wines is detrimental to their quality and can even be a legal issue in some countries. Different methodologies are used in wineries to substitute the classical low-temperature stabilization process, which is an effective but costly process. This study comprises two years of experiments with red wines at an industrial scale. In the first year of the experiment, two subtractive methods (ionic exchange resins and electrodialysis) were tested, whereas two additive methods (potassium polyaspartate and carboxymethyl cellulose, both of them containing gum Arabic) were tested the second year. The tartaric stability of the wines, together with the oenological, chromatic and sensory characteristics, were followed during one year in the bottle. The results indicate that carboxymethyl cellulose and potassium polyaspartate (both combined with gum Arabic) were best at maintaining the sensory and chromatic characteristics during storage, with potassium polyaspartate providing a good tartaric stability to the treated wine and this wine being, in general, preferred in a sensory analysis test.